Emotional Freedom Technique (EFT) Tapping for Post Sectio Caesaria patient: Decrease Anxiety and Increase Early Mobilization - Rusmini Rusmini; Suparmi Suparmi; Ulfah Musdalifah (Jurnal Riset Kesehatan, 2013)
The objective of the study is to evaluate the level of anxiety and early mobilization using the Emotional Freedom Technique (EFT): Tapping on patients post partum post secsio Caesaria before and after intervention period both control and experimental group. Design Quasi-experimental two group design was applied in the study. Forty two mothers with primipara post secsio Caesaria were recruited. Data analysis in the study included correlation, paird t-test, and independent t-test. The findings of the study show that the levels of anxiety and early mobilization in mothers with post secsio Caesaria primipara were significantly different between control and experimental group as well as before and after intervention in experimental group p less than 0.001). Tappingcan be used toreduce theanxietyand and increasedearly mobilizationin Post Secsio Caesaria.